Physical Activity and Cancer - Courneya, Kerry S.; Friedenreich, Christine M.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
This book explores in depth the relation between physical activity and cancer control, including primary prevention, coping with treatments, recovery after treatments, long-term survivorship, secondary prevention, and survival. The first part of the book presents the most recent research on the impact of physical activity in preventing a range of cancers. In the second part, the association between physical activity and cancer survivorship is addressed. The effects of physical activity on supportive care endpoints (e.g., quality of life, fatigue, physical functioning) and disease endpoints (e.g., biomarkers, recurrence, survival) are carefully analyzed. In addition, the determinants of physical activity in cancer survivors (e.g., medical, social cognitive, environmental) are discussed, and behavior change strategies for increasing physical activity in cancer survivors (e.g., counseling, print materials) are appraised. The final part of the book is devoted to further special topics, including the relation of physical activity to pediatric cancer survivorship and to palliative cancer care.
Introduction. Physical Activity and Cancer Prevention: Breast cancer prevention. Genitourinary cancer prevention . Gastrointestinal cancer prevention. Lung cancer prevention. Hematologic cancer prevention. Gynecologic cancer prevention -- Physical Activity and Cancer Survivorship: Breast cancer survivorship. Genitourinary cancer survivorship. Gastrointestinal cancer survivorship. Lung cancer survivorship. Hematologic cancer survivorship. Gynecologic cancer survivorship -- Special Topics: Pediatric cancer survivorship. Palliative cancer care. Physical activity motivation and cancer survivorship. .
Keywords: Medicine; Oncology; Medicine & Public Health; Oncology